Perspective of asylum-seeking caregivers on the quality of care provided by a Swiss paediatric hospital: a qualitative study - Brandenberger, Julia (BMJ Open, 2019)
OBJECTIVES: This study investigated the perspective of asylum-seeking caregivers on the quality of healthcare delivered to their children in a qualitative in-depth interview study. The health of asylum-seeking children is of key interest for healthcare providers, yet knowledge of the perspective of asylum-seeking caregivers when accessing healthcare is limited. SETTING: The study took place in a paediatric tertiary care hospital in Basel, Switzerland. PARTICIPANTS: Interviews were done with 13 asylum-seeking caregivers who had presented with their children at the paediatric tertiary care hospital. Nine female and four male caregivers from Tibet, Eritrea, Afghanistan, Syria, Iraq, Albania and Macedonia were included. A diverse sample was chosen regarding cultural and social background, years of residence in Switzerland and reasons for seeking care. A previously developed and pilot-tested interview guide was used for semistructured in-depth interviews between 36 and 92 min in duration. Data analysis and reporting was done according to Consolidated Criteria for Reporting Qualitative Research. The number of interviews was determined by saturation of data. RESULTS: The interviewees described a mismatch of personal competencies and external challenges. Communication barriers and unfamiliarity with new health concepts were reported as challenges. These were aggravated by isolation and concerns about their child’s health. The following factors were reported to strongly contribute to satisfaction of healthcare delivery: a respectful and trusting caregiver–provider relationship, the presence of interpreters and immediate availability of treatment. CONCLUSIONS: A mismatch of personal competencies and external challenges importantly influences the caregiver–provider relationship. To overcome this mismatch establishment of confidence was identified as a key factor. This can be achieved by availability of interpreter services, sufficient consultation time and transcultural trainings for healthcare workers. Coordination between the family, the government’s asylum system and the medical system is required to facilitate this process.